Validasi Bahan Ajar Fisika Berbasis Konstruktivis dalam Pembelajaran Inkuiri pada Materi Pelajaran Momentum dan Getaran Harmonik Sederhana untuk Meningkatkan Kemampuan Berpikir Kreatif - Widya Oktavia Johan; Hufri Hufri (Universitas Negeri Padang, 2018)
This study aims to determine the value of the validity of constructivist-based physics teaching materials in inquiry learning. The type of research used is research and development (R & D). To achieve this goal, research (R & D) consists of: potential problems, data collection, product design, design validation, product testing, and product revision. The instrument used is a validation sheet that has been validated by experts. Based on the results of validation by experts, the instrument used is having an average value of 90.83 with valid criteria.Based on the data analyzed there are research results, namely the average value of validity of constructivist based physics teaching materials in inquiry learning by experts with an average value of 82.3 and have very valid criteria. It can be concluded that physics-based teaching materials are constructivist in incuri learning in momentum subject matter and simple harmonic vibrations are very valid for use in physics learning in tenth grade on the second terms.